Analiza postopka testiranja sposobnosti bolnikov za uporabo sistema za nadomestno komunikacijo, ki omogoča vodenje računalnika z usmerjanjem pogleda - Groleger, Katja (Rehabilitacija (Ljubljana), 2013)
Background: When an individual can not establish speech and language communication, it is necessary to introduce a system of alternative and augmentative communication. When the individual also has a profound movement disability, the use of an eye-tracking system for the computer is required. Data on pre-trial assessment of functional ability and protocol of potential user testing were not available in the reviewed literature. We wanted to analyse the process of testing and to propose a protocol. Methods: We included all potential users at our Institute in the period from 2010 to mid-2012. We gathered general information on the users and information about their mobility and communication skills. We prepared a questionnaire through which we first collected data on the use of the existing system of augmentative and alternative communication. In the second part, we gathered information about the execution of the testing. Results: We included 15 users, seven children and eight adults. All users had significantly reduced ability of movement, limited to the movement of the head or eye movements. Most of them were using a graphical system for communication. Prior to testing, speech therapists prepared the necessary material. In the testing protocol, the parents, an engineer and occasionally an occupational therapist or teacher were involved. All speech therapists reported that they had difficulties in carrying out the test. The same stands for the users. In seven cases we decided to prescribe the communicator after completing the processof testing. Conclusions: Based on the results of our analysis, we propose selection criteria that could be taken into account in the future with potential users, and some measures to improve the qualityof work, such as more time for preparing and positioning the material, arranging the desktop, adjusting the testing procedures and further training of the staff.
Keywords: augmentative communication; Communication aids for disabled; Computers; eye-tracking; invalidi; komunikacijski pripomočki za invalide; nadomestna komunikacija; protokol testiranja; računalniki; testing protocol; usmerjanje pogleda